Delineating mechanisms of cutaneous wound healing and regeneration in adults - Guerrero-Juarez, Christian Fernando (eScholarship, University of California, 2018)
Regeneration of hair follicles (HFs) and dermal adipocytes (DAs) occurs in mouse skin wounds upon large excisional wounding. Although HF regeneration is observed in African spiny mice of the genus Acomys and northern elephant seals after apex predator-inflicted wounding, laboratory rats do not display such regenerative phenotype. Such regeneration defect was observed in large excisional wound healing models in several rat strains, which undergo otherwise normal wound re-epithelialization. Inter-species transcriptome analyses between laboratory mouse and rat wound tissues attributed such lack of HF regeneration to differences in expression of inflammation markers, epigenetic remodelers and pleiotropic signaling molecules, including Satb1, Setd1b, Setdb1, and Whsc1l1. In mice, the origin of de novo HF regeneration has been partially elucidated, whereas the origin of DAs, a complex tissue that proceeds HF regeneration, remained elusive. Functional lineage tracing revealed the origin of DAs to be myofibroblastic. Bulk RNA-sequencing of genetically-labeled, FACS-purified myofibroblasts across a wound healing time course identified Zfp423 to be markedly up-regulated at a time-point coincident with initiation of DA regeneration. Pharmacological and genetic ablation/down-modulation of BMP signaling resulted in a significant DA regeneration defect. Because the origin of myofibroblasts appears to be tissue- and injury context-specific, the origin of myofibroblasts that contribute to DA regeneration in skin wounds was interrogated. Droplet-enabled single cell transcriptome analyses on unsorted, viable cells from wound dermal tissues collected prior the onset of HF regeneration was performed. Dimensionality reduction analyses revealed a large degree of cellular heterogeneity in the dermal compartment of early stage wounds. Furthermore, sub-clustering of wound fibroblasts further revealed a large degree of fibroblast heterogeneity. Pseudotime analyses revealed a putative fibroblast-myofibroblast differentiation trajectory and identified genes, including transcription factors, that may be important in myofibroblast differentiation in skin wounds in vivo. A subset of myofibroblasts expressed hematopoetic markers, most notably Lyz2, suggesting a common monocytic-origin. Full-length single cell RNA-sequencing and immunoblotting analyses of genetically labeled myofibroblasts confirmed these in silico observations. Bone marrow transplantation and functional lineage tracing using pan-hematopoetic Cre drivers demonstrated labeling of DA in regenerated skin wounds, suggesting that a population of hematopoetic-derived myofibroblasts contributes to regeneration of mouse skin wounds.